2004
DOI: 10.1007/s11661-004-0246-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of strain reversal on the dynamic spheroidization of Ti-6Al-4V during hot deformation

Abstract: The effect of strain-path reversal on the kinetics of dynamic spheroidization during subtransus hot working was determined for Ti-6Al-4V with a colony ␣ structure. Isothermal torsion tests were conducted at a temperature of 815°C and a strain rate of 0.001 s Ϫ1 ; strain-path reversals were achieved by applying forward and reverse torsion sequentially. The kinetics of spheroidization were measured as a function of the local (macroscopic) strain for monotonic-deformation, reversed-torsion, and double-reversed-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 15 publications
4
20
1
Order By: Relevance
“…A summary of the effect of total strain on the extent of dynamic and static spheroidization from the present study and previous works [4,13] is shown in Figure 9. Dynamically spheroidized fractions of alpha grains are compared for different deformation modes and temperatures (Figure 9(a)).…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…A summary of the effect of total strain on the extent of dynamic and static spheroidization from the present study and previous works [4,13] is shown in Figure 9. Dynamically spheroidized fractions of alpha grains are compared for different deformation modes and temperatures (Figure 9(a)).…”
Section: Resultssupporting
confidence: 54%
“…Furthermore, the results obtained in previous work by other researchers suggested, that there is a monotonic strain that is needed to be exceeded for the rapid completion of the dynamic spheroidization process. [4] It can be seen on Figure 9(a) that after exceeding the monotonic strain of 1, the rate of spheroidization significantly increases and is completed by a strain of 2, however, this behavior is only noticeable for the sample that was monotonically strained. In the case where the strain was reversed, the progress of dynamic spheroidization is lower and the rate of spheroidization is constant and similar to the one during prestraining, leading to incomplete spheroidization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Poths et al [27] described the evolution of a fully lamellar microstructure in terms of local continuum strain during hot torsion at 815°C at a strain rate of 10 À3 s À1 . In general, kinking of lamellae was first observed at strains around 0.4 in certain colonies, presumably those in crystallographically soft orientations, but there was no significant change in microstructure.…”
Section: Further Discussionmentioning
confidence: 99%